PERANAN LEMBAGA PEMBERDAYAAN MASYARAKAT (LPM) SEBAGAI MITRA KERJA PEMERINTAHAN NAGARI SARILAMAK KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Eviandi Ibrahim (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research was conducted to analyze the role of community empowerment institutions (LPM) as partners for the Nagari Sarilamak government, Harau sub-district, Lima Puluh Kota district. In this study the author uses an empirical juridical approach. The empirical juridical approach means that apart from looking directly at the review of people's understanding of the settlement of traffic accident cases, the author also looks directly at what is happening in the field. The results of this study are the Role of Community Empowerment Institutions (LPM) in the Position of Community Empowerment Institutions (LPM) as partners of the Nagari Government. Community Empowerment Institute (LPM) Is a forum formed on the initiative of the community as a working partner of the Nagari Government in accommodating and realizing the aspirations and needs of the community in the field of development. This role can be seen in Permendagri Number 18 of 2018 to be precise in articles 4 and 5. The lack of participation of the Nagari community in activities planned by the Community Empowerment Institute (LPM) especially in the implementation of Nagari development planning, because Nagari Sarilamak is the center of the strategic area of the Regency Capital (IKK), of course this has an impact on social problems such as poverty, unemployment, slum areas and high population movements, this is where there are obstacles for the Community Empowerment Institution (LPM) in its role as a partner for the Nagari Sarilamak Government to reach out and establish working relationships with community as a whole. Improving Human Resources (HR) for the Board of Community Empowerment Institutions (LPM) namely as training, Technical Guidance on Community Empowerment Institutions) in order to increase the knowledge and experience of the Management of Community Empowerment Institutions (LPM).Keywords: Role, Institution, Community Empowerment, Work Partners, Government.